2020
DOI: 10.1111/ppe.12703
|View full text |Cite
|
Sign up to set email alerts
|

Severity of nausea and vomiting in pregnancy and early childhood neurobehavioural outcomes: The Growing Up in Singapore Towards Healthy Outcomes study

Abstract: Background Nausea and vomiting of pregnancy (NVP) affects 50 to 80 per cent of women. The existing literature has examined NVP from the perspective of the mother, and relatively less is known about offspring outcomes. Objectives To study the relationships of NVP with social‐emotional, behavioural, and cognitive outcomes of the offspring in a multi‐ethnic Asian cohort. Methods In the Growing Up in Singapore Towards Healthy Outcomes prospective mother‐offspring cohort study, mothers responded to a structured NVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Two studies (n¼9696 children) found that HG-exposed children had significantly lower cognitive development scores than nonexposed children at ages of 2 32 and 9 to 11 years, respectively. 34 Two studies assessed intelligence by measuring intelligence quotient (IQ) scores: the first study (n¼469 children) did not find any differences in IQ scores at age 4, 32 whereas another study (n¼241 children) found that HGexposed children had significantly lower verbal, performance, and full-scale IQ scores than nonexposed children at 3.5 to 7 years of age.…”
Section: Neurodevelopment and Mental Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies (n¼9696 children) found that HG-exposed children had significantly lower cognitive development scores than nonexposed children at ages of 2 32 and 9 to 11 years, respectively. 34 Two studies assessed intelligence by measuring intelligence quotient (IQ) scores: the first study (n¼469 children) did not find any differences in IQ scores at age 4, 32 whereas another study (n¼241 children) found that HGexposed children had significantly lower verbal, performance, and full-scale IQ scores than nonexposed children at 3.5 to 7 years of age.…”
Section: Neurodevelopment and Mental Healthmentioning
confidence: 99%
“…Of the studies included, 12 were cohort studies and 8 caseecontrol studies. HG diagnosis was based on self-reports in 7 studies, 2,22,23,25,28,30,37 interviews in 7 studies, 21,27,29,31,32,34,36 International Classification of Diseases (ICD) codes in 5 studies, 24,26,33e35 and medical records in 1 study. 20 In total, 1,814,785 children were included in this systematic review, of whom 36,546 were born to women who experienced HG.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations